Faktor-Faktor Yang Berhubungan Dengan Perilaku Merokok Pada Siswa Kelas X Di SMKN 5 Denpa - Widyawathi, Tri Ayu (Coping: Community of Publishing in Nursing, 2014)
Smoking behavior is sucking cigarette activities with cigarette holder or cigarette itself which conducted regularly by the smokers in their daily life. The factors that have correlation which smoking behavior among SMK students are stress factor, cigarette knowledge, attitude, cigarette advertisement, cigarette price, cigarette regulation, easy of getting cigarette, family and friends influence. The purpose of research is to analyze the most factor which have correlation with smoking behavior among students at SMKN 5 Denpasar. The research uses descriptive observational  and cross sectional approach. In this research I took the sample to all the students in SMKN 5 Denpasar at X level which are smoking or not. They are 139 students. The data were collected by questionnaire and then analyzed by using multiple logistic regression statistical test with significance level ? ? 0.05. The results of research showed that there are four factors which have relations with smoking behavior, they are cigarette regulation (p=0,010), easy of getting cigarette (p=0,000), family influence (p=0,000) and friends influence (p=0,000). There are five factors which are not related with smoking behavior, they are stress factor (p=0,398), cigarette knowledge (p=0,279), attitude (p=0,417), cigarette advertisement (p=0,935), cigarette price (p=0,617). Based on the researches above I advice to all department at this school to give the information about the dangers of cigarette and do the inspection periodical so we can minimization the increasing of the number of young smoker in Indonesia.
Keywords: The Factors; smoking behavior; students